A comparative assessment of two designs of hip stem using rule-based simulation of combined osseointegration and remodelling. (January 2020) - Chanda, Souptick; Mukherjee, Kaushik; Gupta, Sanjay; Pratihar, Dilip Kumar
The stem–bone interface of cementless total hip arthroplasty undergoes an adaptive process of bone ingrowth until the two parts become osseointegrated. Another important phenomenon associated with aseptic loosening of hip stem is stress-shielding induced adverse bone remodelling. The objective of this study was to preclinically assess the relative performances of two distinct designs of hip stems by addressing the combined effect of bone remodelling and osseointegration, based on certain rule-based criteria obtained from the literature. Premised upon non-linear finite element analyses of patient-specific implanted femur models, the study attempts to ascertain in silico outcome of the hip stem designs based on an evolutionary interfacial condition, and to further comment on the efficacy of the rule-based technique on the prediction of peri-prosthetic osseointegration. One of the two hip stem models was a trade-off design obtained from an earlier shape optimization study, and the other was based on TriLock stem (DePuy). Both designs predicted similar long-term osseointegration (∼89% surface), although trade-off stem predicted higher post-operative osseointegration. Proximal bone resorption was found higher for TriLock (by ∼110%) as compared to trade-off model. The rule-based technique predicted clinically coherent osseointegration around both stems and appears to be an alternative to expensive mechanobiology-based schemes.